Hedging with commodity futures and the end of normal backwardation - Jochen Güntner; Benjamin Karner (Johannes Kepler University of Linz, Department of Economics, 2020)
Using the S&P GSCI and its five component sub-indices, we show that considering each commodity separately yields nontrivial hedging gains in and out of sample. During 1999-2019, the maximum Sharpe ratio portfolio assigns positive weights to the GSCI Energy, Industrial and Precious Metals, whereas only precious metals enter the optimal portfolio after the financial crisis. In out-of-sample optimizations based on dynamic conditional correlations, a subset of commodity futures excluding the GSCI Agriculture and Livestock outperforms conventional stock-bond portfolios with and without the overall GSCI. We argue that the "normal backwardation" in commodity markets has broken down during our sample period.
Keywords: C58; G11; G17; Q02; 330; Commodity futures; Diversification; Hedging; Financial crisis; Normal backwardation